Anxiety sensitivity moderates behavioral avoidance in anxious youth. (November 2015) - Lebowitz, Eli R.; Shic, Frederick; Campbell, Daniel; Basile, Krista; Silverman, Wendy K.
Abstract: Individuals who are high in anxiety sensitivity (AS) are motivated to avoid sensations of anxiety. Consequently, AS is hypothesized to contribute to overall avoidance of any feared stimuli. No studies have yet examined whether fear of a stimulus is a stronger predictor of behavioral avoidance in individuals who are high in AS compared to individuals who are low in AS. We examined whether AS moderates the association between fear of spiders and behavioral avoidance of spider stimuli in 50 clinically anxious youth. Fear of spiders significantly predicted avoidance of spider stimuli in youth high in AS but not in youth low in AS. These results provide support for the role of AS in avoidant behavior and help to explain the link between AS and the anxiety disorders. The results have implications for exposure-based anxiety treatments and highlight the importance of increasing anxious patients' ability to tolerate sensations of anxiety. Highlights: We test whether anxiety sensitivity moderates the link between fear and avoidance. Fear of spiders predicts behavioral avoidance in youth high in anxiety sensitivity. Fear of spiders did not predict avoidance in youth low in anxiety sensitivity.